2020
DOI: 10.1080/15476286.2020.1827785
|View full text |Cite
|
Sign up to set email alerts
|

Introducing differential RNA-seq mapping to track the early infection phase forPseudomonasphage ɸKZ

Abstract: As part of the ongoing renaissance of phage biology, more phage genomes are becoming available through DNA sequencing. However, our understanding of the transcriptome architecture that allows these genomes to be expressed during host infection is generally poor. Transcription start sites (TSSs) and operons have been mapped for very few phages, and an annotated global RNA map of a phagealone or together with its infected host-is not available at all. Here, we applied differential RNA-seq (dRNA-seq) to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 82 publications
(113 reference statements)
1
30
0
Order By: Relevance
“…ncRNA OsiS may harbor a hidden small open reading frame that may drive sedimentation in 30S fractions. Terminator 5′phosphate-dependent exonuclease (TEX) treatment indicates a TEX-unaffected 5′ end downstream of the annotated TSS ( 51 ). Sequencing of RNA fragments recovered from monosomes (Ribo-seq [ 66 ] reanalyzed with HRIBO [ https://github.com/RickGelhausen/HRIBO ]) supports the possibility of a short translated fragment starting at a putative start codon that is out of frame with ptrB .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ncRNA OsiS may harbor a hidden small open reading frame that may drive sedimentation in 30S fractions. Terminator 5′phosphate-dependent exonuclease (TEX) treatment indicates a TEX-unaffected 5′ end downstream of the annotated TSS ( 51 ). Sequencing of RNA fragments recovered from monosomes (Ribo-seq [ 66 ] reanalyzed with HRIBO [ https://github.com/RickGelhausen/HRIBO ]) supports the possibility of a short translated fragment starting at a putative start codon that is out of frame with ptrB .…”
Section: Resultsmentioning
confidence: 99%
“…Stable noncoding RNA fragments overlapping with 59 or 39 untranslated regions (UTRs) constitute a potentially large class of bacterial riboregulators (47)(48)(49)(50). Recent experimental transcriptome annotation (51)(52)(53) suggested that also in the Pseudomonas strain used here, many such UTR-derived candidate ncRNAs exist and accumulate to considerable levels. Here, we observe that such UTR fragments often showed a different sedimentation profile compared to that of the respective coding sequence (CDS) of the same mRNA ( Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, overexpression of the toxin, in the case of the phage vB_KpnP-VAC1, allowed the bacterium to protect themselves from phage infection by the action of the free toxin that inhibited phage infection. Furthermore, the recent study of Wicke et al (2020), demonstrated the reverse effect, i.e. enrichment of ParD antitoxin transcripts of the ParE/ParD type II TA system, leads to successful infection of the strain by the phage, as the viral DNA is protected from the deleterious action of the ParE toxin 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent study of Wicke et al (2020), demonstrated the reverse effect, i.e. enrichment of ParD antitoxin transcripts of the ParE/ParD type II TA system, leads to successful infection of the strain by the phage, as the viral DNA is protected from the deleterious action of the ParE toxin 32 . Besides, it has been described that phage often harbor speci c protease inhibitors that can interfere with the degradation of antitoxins 33 .…”
Section: Discussionmentioning
confidence: 99%